Guidelines for nursing care: an effective tool for the promotion of health in puerperium - Ana Beatriz Querino Souza; Betânia Maria Fernandes (Rev Rene)
The aim of the study was at accessing the feasibility of a guideline of nursing care in the puerperium in primary health care. It is a quasi-experimental research conducted with 168 postpartum women in Juiz de Fora, MG, Brazil, from November 2011 to May 2012. In the intervention group, women were subjected to the guidelines with five puerperal appointments and the control group women were not exposed to the guideline. The results were significant for exclusive breastfeeding, with 42.9% in the intervention group and 25.4% in the control (p=0.002); Panicolaou’s test with 85% in the intervention group and 63.2% in the control (p=0.002); use of ferrous sulfate 26.2% in the intervention group and 18.3% in control (p<0.001). A better vaccination coverage in the intervention group  was also observed. The significant results in most variables show the feasibility of the guideline of nursing care in the puerperium.